Toward More Equitable Language Learning and Teaching Frameworks For Our ELT Community: Moving from EFL to ECL to CE - Mora, Raúl Alberto (GIST – Education and Learning Research Journal, 2022)
Over the past decade, different scholars in ELT have raised questions about the notion of English as a Foreign Language (EFL) and the growing issues related to inequity that such a framework has raised. Our field in Colombia needs to interrogate the very frameworks and concepts we use to define the language and how those definitions will include us or exclude us from the larger global conversations in the field of ELT and related ones as a way to remain active and relevant in years to come. This article proposes moving from English as a Foreign Language (EFL) into English as a Colombian Language (ECL) as the intermediate step toward Colombian English (CE). This article will first problematize EFL as a segue into detailing the transition and some considerations involving our views of English and teacher education.